Pollination ecology of two species of (Orchidaceae): novel mechanisms and underlying adaptations to hummingbird pollination - Nunes, Carlos E. P.; Amorim, Felipe Wanderley de [UNESP]; Mayer, Juliana Lischka Sampaio; Sazima, Marlies (My University, 2015)
Relationships among ﬂoral biology, ﬂoral micromorphology and pollinator behaviourin bird-pollinated orchids are important issues to understand the evolution of thehuge ﬂower diversity within Orchidaceae. We aimed to investigate ﬂoral mechanismsunderlying the interaction with pollinators in two hummingbird-pollinated orchidsoccurring in the Atlantic forest. We assessed ﬂoral biology, nectar traits, nectary andcolumn micromorphologies, breeding systems and pollinators. In both species, nectaris secreted by lip calli through spaces between the medial lamellar surfaces of epider-mal cells. Such a form of ﬂoral nectar secretion has not been previously described.Both species present functional protandry and are self-compatible yet pollinator-dependent. Fruit set in hand-pollination experiments was more than twice that undernatural conditions, evidencing pollen limitation. The absence of fruit set in interspe-ciﬁc crosses suggests the existence of post-pollination barriers between thesesympatric co-ﬂowering species. In Elleanthus brasiliensis, fruits resulting fromcross-pollination and natural conditions were heavier than those resulting from self-pollination, suggesting advantages to cross-pollination. Hummingbirds pollinatedboth species, which share at least one pollinator species. Species differences in ﬂoralmorphologies led to distinct pollination mechanisms. In E. brasiliensis, attachment ofpollinarium to the hummingbird bill occurs through a lever apparatus formed by anappendage in the column, another novelty to our knowledge of orchid pollination. InE. crinipes, pollinarium attachment occurs by simple contact with the bill duringinsertion into the ﬂower tube, which ﬁts tightly around it. The novelties described hereillustrate the overlooked richness in ecology and morphophysiology in Orchidaceae.
Keywords: Epidendroideae; Micromorphology; Nectarsecretion; Ornithophily; Protandry; Sobraliae; Trochilidae.